PYROLYZER PRODUCTION SYSTEM FOR WASTE MANAGEMENT USING GROUP TECHNOLOGY APPROACH - Rifai, Achmad Pratama; Wibisono, Ragil Aditya; Sari, Dwi Kumala; Sari, Wangi Pandan (J@ti Undip: Jurnal Teknik Industri, 2023)
Waste management methods in Indonesia largely rely on unsustainable practices such as open dumping and landfills which urgently need transformation. Pyrolysis is one alternative solution for waste problems as it can process waste into other products. As the existing production system was not set up to manufacture this machine, we proposed a production system to produce a pyrolizer so that a more effective and efficient production process can be achieved. In this study, we employed Group Technology approach using Rank Order Clustering (ROC) method to create cell manufacturing groups. Based on our evaluation on the shortest material movement, we produced 2 different cells to manufacture the pyrolyzer. Cell, I contained plate cutting, drilling, pipe cutting, and bending machines (M2, M5, M3, M4), whilst Cell 2 contained rolling and lathe machines (M1, M6).  It also contained main reactor, pyrolyzer reactor burner, middle condenser, upper access door, bottom access door, upper condenser, bottom condenser components (A, F, H, B, C, G, I). Out of the sixteen components to be made, seven components were in Cell I whereas the other nine were in Cell II (N, P, J, E, D, K , L, M, O) comprising burner case, access ladders, separators, firewalls, reactor base frames, condenser frames, gas piping, water piping, and sprinklers components. By applying this group technology method to the pyrolyzer production system, the production process could be carried out in a more efficient and organized manner.